Motivation, Teachers’ job Performance and Students Academic Performance in Post-Basic Education and Career Development (PBECD), Nigeria - Olamoyegun, Stephania Olabisi; Okolo, Michael Monday; Niyi Jacob Ogunode (Researchparks Publishing, 2023)
This paper looked at the impact of motivation on teachers’ job performance and students’ academic performance in Post-Basic Education and Career Development (PBECD) in Nigeria. The paper employed secondary data. The secondary data were collected from online publications and print materials. The paper concluded that motivation have led to improved teachers’ job performance and students’ academic performance in Post-Basic Education and Career Development (PBECD) in Nigeria. The paper based on this findings recommended that administrators of Post-Basic Education and Career Development (PBECD) in Nigeria should provide teachers with conducive teaching and learning atmosphere for better performances. There should be regular training, workshops and seminars for the principals of Post-Basic Education and Career Development (PBECD) on the use of different motivational techniques for the improvement of teacher’s job performance. Motivational techniques should be administered properly by the principals of Post-Basic Education and Career Development (PBECD) in order to improve the students’ academic performance. Government at various levels should endeavor to adequately motivate the principals of Post-Basic Education and Career Development (PBECD) by providing instructional materials to schools in due time which could result to better students’ academic performance.